2011
DOI: 10.7763/ijcea.2011.v2.126
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Methylene Blue from Effluent by Using Activated Carbon and Water Hyacinth as Adsorbent

Abstract: Activated carbon has been widely used as a good adsorbent. Water hyacinth may be an alternative of activated carbon. This work deals with the study of methylene blue adsorption on activated carbon as well as water hyacinth ash from aqueous solution. Batch kinetic and isotherm studies were carried out at different conditions like, contact time, methylene blue concentration etc for both adsorbents. The Freundlich and Langmuir adsorption models have been mathematical description of adsorption equilibrium and fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 5 publications
(6 reference statements)
1
19
0
1
Order By: Relevance
“…Low et al (1995), reported the biosorption of basic dyes (methylene blue and Victoria blue) by water hyacinth roots with maximum sorption capacities of 128.9 and 145.9 mg/g respectively. Kanawade and Gaikwad (2011) also reported that the adsorption data of methylene blue by water hyacinth roots correlated well with the Langmuir and Freundlich isotherms. Sivaraj et al (2010), reported the removal of reactive Magenta B and reactive Turquoise Blue dyes using activated carbon obtained from water hyacinth.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Low et al (1995), reported the biosorption of basic dyes (methylene blue and Victoria blue) by water hyacinth roots with maximum sorption capacities of 128.9 and 145.9 mg/g respectively. Kanawade and Gaikwad (2011) also reported that the adsorption data of methylene blue by water hyacinth roots correlated well with the Langmuir and Freundlich isotherms. Sivaraj et al (2010), reported the removal of reactive Magenta B and reactive Turquoise Blue dyes using activated carbon obtained from water hyacinth.…”
Section: Introductionmentioning
confidence: 55%
“…High efficiency, availability and low cost have been major reasons for the use of plants, agricultural and biological materials as adsorbents for aqueous pollutants. Dye effluents in aqueous streams represent another group of water pollutants that require great attention by virtue of the large amount of production and use of dyes globally (Imamura et al, 2002;Kanawade & Gaikwad, 2011). The reduction of light penetration in water bodies, especially to benthic organisms and the low biodegradability of dyes present them as potential toxicants to marine lives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are widely used in various industries such as textile, plastic, paper and rubber industries [1]. Among these industries, textile industry ranks first in the usage of dyes for coloration of fiber.…”
Section: Introductionmentioning
confidence: 99%
“…The scientific articles often compared natural sorbents adsorption to adsorption on activated carbon [17]. The ability of P. oceanica to remove the dye C.I.…”
Section: Introductionmentioning
confidence: 99%